FEATURES AND CHARACTERISTICS OF A LABORATORY PHYSICS WORKSHOP IN THE STUDY OF PHYSICS ESHTUXTAROVA ORZIGUL SHONAZAROVNA - Umirov Homid (Western European Studies, 2024)
Laboratory work is a teaching method in which students understand physical phenomena. Laboratory work is a teaching method in which students understand physical phenomena. At the frontal laboratory work, concepts are formed as the main element of scientific knowledge, the initial ideas about phenomena are developed and deepened, the connection between science and technology is traced, interest is developed that promotes independent activity, and in general the gap between theory and practice is overcome.
Keywords: laboratory work; training and education; environmental education